Arthroscopic-assisted reduction and fixation of proximal tibial fractures: personal surgical technique. - Compagnoni, Riccardo; Maione, Alessio; Calanna, Filippo; Ferrua, Paolo; Randelli, Pietro Simone (Acta Biomedica Atenei Parmensis, 2021)
Purpose The purpose of this study was to describe the authors’ arthroscopic-assisted reduction and fixation (ARIF) technique in the treatment of type Schatzker I-III tibial plateau fractures, with the use of instruments commonly used in anterior cruciate ligament reconstruction, evaluating clinical and radiological outcomes on four patients at short-term follow-up. Methods A retrospective analysis was performed in our Institution considering 4 patients who underwent ARIF procedure between 2018 and 2020 at minimum 3 months of follow-up. All patients were evaluated clinically (Rasmussen Score, VAS and Crosby-Insall Grading) and radiographically (after surgery and at 6 weeks). Results Mean follow-up was 9 months (range 6-12 months). Rasmussen score and VAS were respectively 26 (Excellent) and 1 at the last follow-up. According to the Crosby-Insall Grading System, all patients reported excellent results. At final control the mean ROM in the injured knee was 125°(range 100°-140°). Mean hospitalization was 2 days (range 1-4 days). No adverse events were reported. Conclusions ARIF is a reliable technique for tibial plateau fracture (Schatzker I-III). The technique described is very cheap and reproducible in any hospital . This procedure allows to well understand the pattern of fracture and to obtain an anatomical reduction with a great tissue sparing and a faster recovery of knee function. Level of Evidence: Level IV Keywords: tibial plateau fractures, treatment, arthroscopy, surgery, artrhoscopic-assisted